Surveying Cory Shearwater colonies with camera traps and identifying potential invasive nest predators - Lamelas-López, Lucas (2023)
Background The Azores holds the largest population of Cory's shearwater Calonectris borealis (Cory, 1881) (Aves, Procellariiformes, Procellariidae) in the world. One of the major threats of this species in the Azores is the predation by invasive mammals, which were introduced during European colonisation of the islands. The present study provides a dataset from a camera-trapping survey performed in colonies of Cory’s shearwater. The sampling was conducted between 7 April and 23 October 2019, covering the entire breeding season, in three colonies of the Terceira Island (Azores). A total of 32 nests were sampled using motion-triggered cameras. The aims of this study are to provide information about the ecological patterns of the Cory shearwater and to identify potential nest predators. New information Our results include a total of 6972 records of 15 species (nine species of birds, five of mammals and one reptile), of which 5414 records are of Cory’s shearwater, 478 of potential mammal predators and 1080 of another vertebrate species. Information about the biology of the species is also provided, as species circadian behaviour and habitat description.